The terms and relations of comparison, referential, and relative processes - Guillermina Jasso (Institute for the Study of Labor (IZA), 2007)
This paper develops the mathematical foundations of comparison, referential, and relative (CRR) processes. The key ingredients are: (1) three kinds of terms; and (2) two kinds of relations. Combining the three terms - absolute amount, relative amount, and relative rank - with the two kinds of relations - functions of one variable and functions of two variables - produces a set of six fundamental CRR processes. The paper analyzes the appropriate general functions for each of the six basic CRR processes, and explores the theoretical criteria for specific functions. The paper takes three further steps. First, it links the six basic types of CRR processes to the three fundamental sociobehavioral forces in the recently proposed new unified theory, which also links the forces to identity and to happiness. Second, following the new unified theory, the paper shows how change over time in the fundamental sociobehavioral outcomes provides new manifestations of CRR processes. Third, the paper describes how the primordial sociobehavioral outcomes, like their change over time, operate as explanatory factors that generate rich new phenomena, including new emergent subgroups and new inequalities.
urn:nbn:de:101:1-20080401134
Keywords: 330; Maßzahl; Disparitätsmaß; Soziales Verhalten; Lebenszufriedenheit; Theorie